2021
DOI: 10.26574/maedica.2021.16.4.620
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inflammatory Markers with COVID-19 Outcome among Hospitalized Patients: Experience from a Tertiary Healthcare Center in Western India

Abstract: Introduction: COVID-19 is a highly infectious disease and varies in the severity of presentation as well as survival outcome due to varied inflammatory responses. Hence, the present study is aimed to evaluate the role of inflammatory markers in predicting the outcome of COVID-19 in hospitalized patients.Methods: A total of 272 confirmed COVID-19 patients were included in the study. Clinical and demographic data were collected. Biochemical, hematological, and inflammatory markers were assessed in all patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(23 reference statements)
3
4
0
Order By: Relevance
“…Furthermore, IL-6 has the greatest sensitivity in predicting mortality among COVID-19 patients. Our results are in accordance with those of Sakthivadivel et al (2021) [6], and demonstrate the potency of IL-6 as a predictor for disease severity and mortality in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, IL-6 has the greatest sensitivity in predicting mortality among COVID-19 patients. Our results are in accordance with those of Sakthivadivel et al (2021) [6], and demonstrate the potency of IL-6 as a predictor for disease severity and mortality in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Males predominate as patients with COVID-19, and are therefore associated with a more severe form of the disease, similar to the study by Sakthivadivel et al (2021) [6]. The proportion of middle-aged patients with co-morbidities was significantly higher among non-survivors in comparison with survivors [13,14].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The non-survivors were significantly older (61.77 ± 13.89 years) than the survivors (49.91 ± 15.10 years). This is consistent with the previous studies documenting the age-related increase in COVID-19 mortality [4,5]. This could be attributed to natural immunity steadily weakening with age, making older persons more prone to developing more severe illnesses [6].…”
Section: Discussionsupporting
confidence: 93%
“…Identifying crucial laboratory indicators for disease severity at an early stage might assist in monitoring and preventing disease development towards a severe form in the lack of a targeted medication for the illness. Studies have shown that many laboratory indicators, including the total leucocyte count, C-reactive protein (CRP), urea, creatinine, interleukin-6 (IL-6), platelet count, D-dimer, ferritin, random blood sugar levels, and CT-severity score are connected to illness prognosis and outcome [3,4]. The current study was carried out to determine the association of clinical and inflammatory profiles with the outcome of COVID-19 infection.…”
Section: Introductionmentioning
confidence: 98%